(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This research paper focuses on, thermodynamic properties such as heat of formation of tetrahedral semiconductors were evaluated. An interesting empirical relationship it was proposed as a method of calculating the heat of formation for All BVl, Alll BV, Al Blll CVl 2 and semiconductors with tetrahedral structure using their lattice constant. We used the proposed model to quantify the heat of formation on binary and ternary chalcopyrite semiconductors. The formation’s heat (- Hf in KJmol) for these compounds exhibits As compared to the lattice constant, the relationship is linear (in Ao), which lies on the straight line. The available test and hypothetical qualities recorded by past analysts were discovered to be in fantastic arrangement.